Temporal sampling of root exudates using coated blade-SPME for decoding plant–pathogen interactions - Halane, Hodan; McDowell, Tim; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2025)
Root exudates shape the rhizosphere and mediate plant–microbe interactions, yet traditional sampling techniques often disturb the natural environment. Here, we present the use of coated blade-solid-phase microextraction (CB-SPME) method for passive, non-invasive in situ temporal metabolomic profiling of pea (Pisum sativum) root exudates during infection by the soil-borne pathogen Aphanomyces euteiches. In comparison to previously established extraction techniques, CB-SPME delivered lower absolute recovery but superior reproducibility while maintaining sensitivity. This non-destructive approach preserves rhizosphere integrity, enabling continuous monitoring of dynamic metabolite fluctuations and offers new insights into how root exudate influences plant–microbiome interactions.